Adults' and children's perceptions of barriers and facilitators of school‐aged children's physical activity in an inner‐city urban area. Issue 1 (21st November 2019) - Duck, Angela Allen; Robinson, Jennifer C.; Stewart, Mary W.
Abstract: In the United States, obesity rates among children remain a pressing public health concern Compounding that, disparities exist with higher childhood obesity among minority and lower socioeconomic neighborhoods. Physical activity is associated with more favorable weight status in children and adolescents. Purpose: This study aimed to identify and explore factors that influence physical activity in children in a low‐income neighborhood. Design and Methods: An exploratory descriptive qualitative design was employed using Photovoice and focus group interviews to identify barriers and facilitators of physical activity. Results: Eight adults and five children enrolled in the study. Photovoice was used to prompt discussions during the focus groups. Analysis of verbatim transcripts included constructed coding with categorization into themes. Four themes of (a) knowledge, (b) play, (c) opportunities and a changing environment, and (d) resources were identified. Among children, three themes from the children's focus group were identified as (a) knowledge, (b) play, and (c) environment. This study found both resource and knowledge challenges, as well as a strong commitment to providing physical activity opportunities. Practice Implications: Continued efforts are needed to develop and implement physical activity interventions to reduce obesity and improve health among children in impoverished, urban areas.